Hydrochemistry and Characteristics of Groundwater: Case Study Water Contamination at Citarum River Upstream - Hadian, Mohamad Sapari Dwi; Waliana, T Yan; Sulaksana, Nana; Putra, Dewandra Bagus Eka; Yuskar, Yuniarti (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
Rancaekek and Sayang area, West Java, are the area where many industrial factories are located.Thus, the region becomes the targeted destination for industrial development.The  population in the area is rising due to the growth of industries causing the regional development becomes uncontrollable. In addition, the constant increment of waste and also poor-coordinated disposal systems may result in groundwater contamination in the areas. The rapid growth of the area increase the need for groundwater as well as the need for more research about contamination at Rancaekek and Sayang. The research aims to explore the spread of groundwater contamination in the area. The research method is carried out based on the analysis of Geological Mapping, Hydrogeological Mapping and chemical characteristics of the groundwater in the area. Chemical analyses of the groundwater were conducted through laboratory test of groundwater samples at specific spots of dug wells. The lab test results were further analyzed to determine the contamination zone. The findings reveal that the distribution of contamination in the area follow the shallow ground water flow patterns, the water contamination contains heavy metal and there is degradation of soil fertility. The findings suggest the stakeholders to delineate the contaminated area, and increase the dissemination of environmental awareness.